Changes in the blood coagulation system and non-specific plasma proteinases in ischemia-reperfusion injury - Pisarev, A. A.; Petrenko, V. I.; Kubyshkin, A. V.; Kharchenko, V. Z.; Fomochkina, I. I.; Kuzichkin, D. S. (Bi͡u︡lletenʹ Sibirskoĭ medit͡s︡iny, 2020)
The aim of this study was to determine the general patterns of pathogenetic changes in the blood coagulation system and in non-specific proteinases and their inhibitors during the development of experimental  ischemiareperfusion injury.Materials and methods. The study was conducted on 48 male Wistar rats (180–200 g). We used a model of ischemia-reperfusion injury achieved by applying rubber tourniquets to both hind limbs at the inguinal fold level for 6 hours. Revascularization was performed for 6, 12, or 24 hours following the application of tourniquets, after which we examined the state of the internal and external blood coagulation pathways and the activity of nonspecific proteinases and their inhibitors.Results. Indicators of blood coagulation system change show the development of blood hypocoagulation changes as the reperfusion time increases. By the 6th hour of reperfusion, the prothrombin time (PT) was lengthened by 112.0% (p = 0.0142) and the activated partial thromboplastin time (APTT) by 170.0% (p = 0.0147) compared with values in the control group. By the 12th reperfusion hour, the PT was lengthened by 174.2% (p = 0.0389), and the APTT increased 4.9-fold (p = 0.0002). When the reperfusion period was increased to 24 hours, it was characterized by lengthened PT and APTT, accompanied by an increase in antithrombin III by 11.5% (p = 0.0371) and a decrease in protein C by 71.4% (p = 0.0071). Changes in the non-specific proteinases and their inhibitors were characterized by a 2.8-fold increase in the trypsin-like proteinase activity (p < 0.001) relative to the control, as well as a 2.2-fold decrease in antitrypsin activity and acid-stable inhibitors (p < 0.001), which reached a maximum after 24 hours of reperfusion. A direct correlation was found between indicators characterizing the deficiency of coagulation system factors and a decrease in antiproteinase potential.Conclusion. Hemostatic system disorders are characterized by the development of hypocoagulation during ischemia-reperfusion injury as the result of an increase in the trypsin-like proteinase activity and a decrease in the levels of inhibitors. The established changes may be associated with the deficiency of coagulation factors and proteinase inhibitors and share common pathogenic mechanisms.